2019
DOI: 10.1103/physrevd.100.084009
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of gravitational waves in Chern-Simons axion Einstein gravity

Abstract: In this paper we shall investigate the propagation of gravitational waves in a flat Friedman-Robertson-Walker background, in the context of a string motivated corrected Einstein gravity. Particularly, we shall consider a misalignment axion Einstein gravity in the presence of a string originating Chern-Simons coupling of the axion field to the Chern-Pontryagin density in four dimensions. We shall focus our study on the propagation of the gravitational waves, and we shall investigate whether there exists any dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…As was shown in [114], the axion field can affect the maximum allowed mass for the neutron star. In addition, in [18], it was shown that the axion field causes inequivalent propagation in the circularly polarized gravitational wave modes. Both the neutron star and gravity waves issues are timely, and perhaps should be further be studied in the axion perspective.…”
Section: Brief Discussion On Future Perspectives: Neutron Stars mentioning
confidence: 99%
See 1 more Smart Citation
“…As was shown in [114], the axion field can affect the maximum allowed mass for the neutron star. In addition, in [18], it was shown that the axion field causes inequivalent propagation in the circularly polarized gravitational wave modes. Both the neutron star and gravity waves issues are timely, and perhaps should be further be studied in the axion perspective.…”
Section: Brief Discussion On Future Perspectives: Neutron Stars mentioning
confidence: 99%
“…The non-trivial polarization of gravitational waves in theories involving Chern-Simons axionic couplings is also discussed in the literature [72]. For an important stream of paper on Chern-Simons coupling terms see [18,72,[75][76][77][78][79][80][81][82][83][84][85][86][87]. Moreover, the axions can be related with the H 0 -tension problem [88].…”
Section: Introductionmentioning
confidence: 99%
“…Our aim is to solve numerically the differential equation (33) in the redshift interval z ¼ ½0; 10, by using appropriate physical motivated initial conditions which correspond to the late stages of the matter domination era. These are…”
Section: Early and Late Dark Energy Erasmentioning
confidence: 99%
“…Compactifications in string theory generically predict the existence of axions in 4-dimensional low-energy effective field theory. The gravitational Chern-Simons coupling commonly arises in the string axiverse as the Chern-Pontryagin density [18,19], which can affect tensor perturbations during their propagation [20][21][22][23][24][25][26][27][28]. Due to the weakness of gravitational interaction, the string corrections are weakly constrained.…”
Section: Introductionmentioning
confidence: 99%